Dialysis Provision and Implications of Health Economics on Peritoneal Dialysis Utilization: A Review from a Malaysian Perspective. (31st October 2017) - Abdul Manaf, Mohd Rizal; Surendra, Naren Kumar; Abdul Gafor, Abdul Halim; Seong Hooi, Lai; Bavanandan, Sunita
Abstract : End-stage renal disease (ESRD) is managed by either lifesaving hemodialysis (HD) and peritoneal dialysis (PD) or a kidney transplant. In Malaysia, the prevalence of dialysis-treated ESRD patients has shown an exponential growth from 504 per million population (pmp) in 2005 to 1155 pmp in 2014. There were 1046 pmp patients on HD and 109 pmp patients on PD in 2014. Kidney transplants are limited due to lack of donors. Malaysia adopts public-private financing model for dialysis. Majority of HD patients were treated in the private sector but almost all PD patients were treated in government facilities. Inequality in access to dialysis is visible within geographical regions where majority of HD centres are scattered around developed areas. The expenditure on dialysis has been escalating in recent years but economic evaluations of dialysis modalities are scarce. Evidence shows that health policies and reimbursement strategies influence dialysis provision. Increased uptake of PD can produce significant economic benefits and improve patients' access to dialysis. As a result, some countries implemented a PD-First or Favored Policy to expand PD use. Thus, a current comparative costs analysis of dialysis is strongly recommended to assist decision-makers to establish a more equitable and economically sustainable dialysis provision in the future.